Pemilihan Sistem Monitoring Organisasi dengan Technique For Others Reference By Similarity To Ideal Solution (TOPSIS) - Primawati Utami, Teja (Cendekia Niaga, 2020)
The covid pandemic in the world requires of social restrictions. Working from home is one solution in doing work. Every employee is required to contribute to the organization by always maintaining their performance. Therefore, monitoring is important to do to assess the performance results of these employees. Three monitoring alternatives are presented, namely, monitoring by means of self-uploading of performance results, monitoring with confirmation from supervisor and automatic monitoring applications during work implementation. The TOPSIS decision making method is used to select the three alternatives with 8 criteria. Based on the results of calculations and TOPSIS analysis, it was found that the automatic monitoring application during work was the best monitoring that needed to be made and to be implement. The value of relative proximity to the positive ideal solution of 0.63139.